From the “reception trap” to the “denied reception”. The tightening of migration policies and the centrality of informal settlements between segregation and resistance - Firouzi Tabar, Omid (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2025)
Abstract Alongside the external borders of Italy, but also across its internal territories, we are witnessing an evolving process of production of new social relations and new micro-spatialities that tend to progressively change the territorial features. This new “presence” of asylum seekers across the urban spaces and the new strategies adopted to control it lead us to question the evolutions (and weakness) of that securitarian rhetorics and policies that have been at the center of the migrations government in Italy, for many years. Security policies that in recent years seem to have found new vigour and a certain hegemony even with respect to the right to asylum and reception.This paper, based on the observations collected during an ethnographic research carried out in Padua, explores the social implications of the frame of segregation, social abandonment and urban dispersion that characterize asylum seekers (and ex asylum seekers) daily surviving and resisting accross the urban areas. Moreover we focus on the ways in which this internal “borderscapes” has become in certain cases a urban “battleground” that makes less linear the urban governance of the migrants within the securitarian paradigm. In this sense we have looked at the counter-conduct put in place against the lack of freedom and the violation of the rights especially for those excluded fron the institutionale reception system, so turning our gaze outside the reception facilities dealing with those who, forcibly or voluntarily, are populating the informal settlements that now materialize in Padova and many other Italian cities.